2005
DOI: 10.1253/circj.69.339
|View full text |Cite
|
Sign up to set email alerts
|

Reference Value for C-Reactive Protein and Its Distribution Pattern in Thai Adults

Abstract: -reactive protein (CRP) is an acute-phase constituent that has been measured for more than 70 years in the diagnosis and monitoring of active infection and inflammation 1 because it is one of the most fundamental and earliest host responses to inflammatory injury. It is mainly regulated by the CRP gene, located on the long arm of chromosome 1, induced at the transcriptional level by interleukin-6 (IL-6), and its major synthetic site is the heptocyte. 2,3 In fact, it is released into the circulation with equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Fig. 2 shows the median concentrations of all CRP values from study participants and those study participants who had CRP< 10 mg/L in comparison with the published data from countries such as Germany [18], Japan [19], Thailand [20], UK [18] and USA [21,22]. The median CRP values in Aboriginal Australians were substantially higher than those in other populations reported in the literature.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Fig. 2 shows the median concentrations of all CRP values from study participants and those study participants who had CRP< 10 mg/L in comparison with the published data from countries such as Germany [18], Japan [19], Thailand [20], UK [18] and USA [21,22]. The median CRP values in Aboriginal Australians were substantially higher than those in other populations reported in the literature.…”
Section: Discussionmentioning
confidence: 81%
“…On the contrary, in a study in the Japanese population, CRP levels are significantly higher among men than among women [19,25]. No gender differences were found in several other populations [18,20,[26][27][28][29]. The causes of higher CRP levels in Aboriginal women remain to be determined.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, these relationships were never evaluated in a model of obesity. Previous investigations have indicated that fasting levels of CRP, TNF-a, and sTNF-R1 are not significantly modulated during the EHC (26)(27)(28)(29)(30)(31). Therefore, in the present study, CRP, TNF-a, and sTNF-R1 concentrations were only evaluated in a fasted state.…”
Section: Discussionmentioning
confidence: 85%